A diagnosis reconsidered: the symptomatic gallbladder remnant. (3rd April 2019) - Grossman, Julie G.; Johnston, William R.; Fowler, Kathryn J.; Williams, Gregory A.; Hammill, Chet W.; Hawkins, William G.
Abstract: Background: Patients can present with symptomatic gallbladder disease after cholecystectomy due to a remnant gallbladder. This is a rare problem and challenging diagnosis with limited prior characterization; thus, we present a large series of patients with a gallbladder remnant. Methods: A retrospective review was performed of all patients presenting with symptomatic gallbladder remnant at a tertiary care center from 2002 to 2016. Data on presenting symptoms, diagnostic tests, treatments, and follow‐up were collected. Results: Thirty‐one patients diagnosed and treated for a symptomatic gallbladder remnant were identified. The most common presenting symptoms included right upper quadrant pain (87%) and nausea (55%). The median time from symptom presentation to definitive diagnosis was 60 days. Diagnostic modalities utilized in the evaluation of these patients demonstrated that endoscopic retrograde cholangiopancreatography and magnetic resonance cholangiopancreatography were effective with sensitivities of 85% and 90%,  respectively. Twenty‐three (76.2%) patients underwent completion cholecystectomy, which proved to be definitive treatment. Additionally, eight (25.8%) patients were non‐operative candidates and underwent endoscopic retrograde cholangiopancreatography and sphincterotomy, three of whom developed recurrent symptoms. Conclusion: A symptomatic gallbladder remnant after cholecystectomy is infrequently seen; however, the diagnosis should be considered in patients with recurrent biliary symptoms after cholecystectomy. Completion cholecystectomy can be challenging but is highly effective for definitive treatment. Abstract : Highlight Although a symptomatic gallbladder remnant after cholecystectomy is rare, the diagnosis should be considered in patients with recurrent biliary symptoms after cholecystectomy. Completion cholecystectomy can be challenging but is highly effective for definitive treatment. Grossman and colleagues hope to heighten awareness of this entity in the differential diagnosis of post‐cholecystectomy syndromes.